2022
DOI: 10.1371/journal.pone.0273152
|View full text |Cite
|
Sign up to set email alerts
|

Timely initiation of antenatal care and associated factors among pregnant women attending antenatal care in Southwest Ethiopia

Abstract: Background The timing of initiation of first antenatal care visit is paramount for ensuring optimal care and health outcomes for women and children. However, the existing evidence from developing countries, including Ethiopia, indicates that most pregnant women are attending antenatal care in late pregnancy. Thus, this study was aimed to assess timely initiation of antenatal care and associated factors among pregnant women attending antenatal care services in Southwest Ethiopia. Methods Institutional based c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…Women with zero parity were likelier to start receiving ANC services on time than women with high parity (one or more). This conclusion aligns with research from Ethiopia [ 18 , 31 , 38 ], Saudi Arabia [ 21 ], Ghana [ 24 ], and Myanmar [ 26 ]. This conclusion may be explained by the fact that women who have never been pregnant or birth before are likelier to be anxious about finding out whether they are pregnant and to think that starting ANC as soon as possible is crucial.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Women with zero parity were likelier to start receiving ANC services on time than women with high parity (one or more). This conclusion aligns with research from Ethiopia [ 18 , 31 , 38 ], Saudi Arabia [ 21 ], Ghana [ 24 ], and Myanmar [ 26 ]. This conclusion may be explained by the fact that women who have never been pregnant or birth before are likelier to be anxious about finding out whether they are pregnant and to think that starting ANC as soon as possible is crucial.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding the timely initiation of ANC service, knowledgeable women were likelier to initiate ANC service in a timely manner compared with nonknowledgeable women. This finding is again supported by studies conducted in Ethiopia [ 14 , 19 , 27 , 35 , 38 ]. A possible justification might be that women who have good knowledge of maternal healthcare are directly linked to higher maternal healthcare utilisation because knowledgeable women might have a better understanding of their health, which contributes to their acceptance and utilisation of healthcare services.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Previous studies from LMICs reported significant associations between timely initiation of ANC attendance by pregnant women and women’s age, 17 , 18 , 20 , 22–25 , 30–32 , 37 wealth status, 18 , 24 , 25 , 31 , 33 , 37 education, 18 , 21–25 , 29 , 31 parity, 18 , 20 , 23–27 , 29 , 32 access to media, 23 , 24 , 28 , 31 , 38 pregnancy intention, 16 , 19 , 21 , 23 , 24 , 26 , 27 , 29–31 , 39 residential area, 24 , 29 , 36 family size, 17 , 29 and husband’s education. 19 , 36 Except for the statistically insignificant correlation of husband’s education with pregnant women’s timely ANC attendance, our findings on the higher odds of pregnant woman’s timely ANC attendance by age, education, wealth status, parity, pregnancy intention, residential area, and access to media were fairly consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%